Effect of carbon nanotubes and aluminum oxide on the properties of a plasma sprayed thermal barrier coating. Issue 1 (January 2018) - Thakare, J.G.; Mulik, R.S.; Mahapatra, M.M.
Abstract: To protect the structural components of a power generating unit from the corrosive environment, thermal spray coatings are applied to the components. In the present work, four different types of thermal barrier coating (TBC) viz. partially stabilised zirconia (8YSZ), zirconia-20% alumina (ZA) composite coating without carbon nanotube (CNT) reinforcement, and ZA with 1% and 3% CNT reinforcement. The coating was deposited on NiCrAlY coated P91 steel using a plasma spraying process. The coating microstructure and phases were characterised using field emission scanning electron microscope (FE-SEM) with energy dispersive spectroscopy (EDS). The phases of the coating were analyzed using X-ray diffraction technique. The effect of CNT reinforcement on the thermal conductivity, porosity, and hardness of the composite coatings was investigated. The protective behavior of the coatings was characterised by potentiodynamic polarization testing and electrochemical impedance measurements. The thermal conductivity of the composite coating was found to be increased with increasing CNT content. Hardness was found to be highest for 3% CNT reinforcement and the thermal conductivity was found to increase with decreasing porosity. The electrochemical measurements indicate that reinforcement of CNT in zirconia alumina composite coating improved its corrosion resistance.